The role of the core competence and core resource features of a sharing economy on the achievement of SDGs 2030 - Ching-Chi Hsu (Journal of Innovation & Knowledge (JIK), 2023)
Globally, sustainable development goals (SDGs), which need to be achieved using the sharing economy, are the focus of many recent studies. This article investigates the impact of sharing economy features such as core competence and resources on achieving SDGs in the tourism industry in the BRICS countries (Brazil, Russia, India, China, and South Africa). It examines the mediating impact of distinctive competitive advantage between the core competence and core resource features of a sharing economy, and achievement of the SDGs. The study also examines the moderating role of institutional support on the nexus of distinctive competitive advantage and achievement of SDGs in the BRICS countries. Questionnaires are used to collect primary data and Smart-PLS is used to analyse the data. The results indicate that the core competence and core resource features have a positive association with the achievement of SDGs, and that distinctive competitive advantage significantly mediates the association between core competence, core resources, and achievement of the SDGs. The outcomes reveal that institutional support significantly moderates the nexus of distinctive competitive advantage and achievement of SDGs. The research provides guidelines for regulators establishing policies related to the achievement of SDGs using the sharing economy.
Keywords: 650; Achievement of SDGs; Core competence; Core resources; Distinctive competitive advantage; Institutional support; Sharing economy